Hunting the elusive shallow n-type donor – An ab initio study of Li and N co-doped diamond - Conejeros S.; Othman M.Z.; Croot A.; Hart J.N.; O'Donnell K.M.; May P.W.; Allan N.L. (Elsevier Ltd, 2024)
Indexed by WOS/SCOPUS/ERA